Mineral salt intake effects on faecal-N concentration and the volume and composition of beef cattle urine - da Silva Cardoso, Abmael [UNESP]; José Neto, Antônio; Azenha, Mariane Vieira; Morgado, Eliane Silva; Brito, Liziane de Figueiredo; Janusckiewicz, Estela Rossetto; Berchielli, Telma Terezinha [UNESP]; Reis, Ricardo Andrade [UNESP]; Ruggieri, Ana Cláudia [UNESP] (Springer Nature, 2018)
The effect of mineral salts on water ingestion and urine volume in cattle has been extensively studied. However, recently, this effect has been investigated as a potential mitigator of environmental aspects related to the nitrogen (N) cycle, such as nitrate (NO3 −) lixiviation, ammonia (NH3) volatilisation, and nitrous oxide (N2O) emissions. The effect of mineral salts, particularly sodium chloride (NaCl), on urine-N concentration, urine volume, the proportion of N compounds in the urine, and faecal-N concentration has not yet been explored in field conditions with respect to environmental aspects of beef cattle production. The present study investigated the effect of dietary mineral salt rates on these parameters. A Latin square (5 × 5) experimental design was utilised with five concentrations of mineral salts in the diet: 0.0, 2.0, 4.0, 6.0, and 8.0 g based on dry matter (DM) ingestion (g/kg DM). The nitrogen concentration in the urine and urine volume increased linearly. The total N excreted (g/day) via urine did not vary with increasing mineral salt concentrations. When evaluated, the N compounds of urine (urea-N, allantoin-N, and hippuric acid-N) also reacted to the increased mineral salt concentrations, while creatinine-N did not. Urea-N, allantoin-N, and hippuric acid-N linearly increased their proportions in total N-urine. The N concentration in faeces was not affected by mineral salt concentrations. The urine volume, concentration of N, and proportion of N compounds in the urine affected N2O emissions and NH3 volatilisation. Therefore, mineral salt utilisation may be an option for mitigating N pollution from beef cattle, especially for grasslands in tropical countries.
Keywords: Nitrogen usage efficiency; Sodium chloride; Urea-N; Urinary N compounds